The animals we eat: between attention and ironic detachment. - Caprioglio Panizza, Silvia (My University, 2022)
This article engages with two fundamental attitudes toward animals who are used for human consumption: attention and ironic detachment. Taken as polarities linked with animal consumption and the refusal thereof, I discuss how these two attitudes are shaped and manifested during moments of encounter with the animals in question. Starting from a striking photograph from the Lychee and Dog Meat Festival in China, I explore the embodiment of these attitudes in the “gaze” of human participants during the encounter with animals who are going to be killed for food.
Zvířata, která jíme: mezi pozorností a ironickým odstupem.
Keywords: attention; irony; vegetarianism; gaze; encounter; Iris Murdoch; pozornost; ironie; vegetariánství; pohled; setkání; Iris Murdochová